Impact of Drawing Occupational Therapy on Auditory Hallucinations Among Mental Health Patients - Bunga Yusnanda; Milkhatun Milkhatun; Arief Budiman; Dwi Rahmah Fitriani (Jurnal Keperawatan Profesional, 2026)
Auditory hallucinations are a common positive symptom of schizophrenia that can impair psychosocial functioning and increase the risk of aggressive behavior. Drawing-based occupational therapy has been proposed as a simple nonpharmacological intervention to help patients manage hallucinations. This study evaluated the implementation of drawing-based occupational therapy in reducing the severity of auditory hallucinations in a client with schizophrenia using a psychiatric nursing care approach. A single-case study was conducted involving one client diagnosed with schizophrenia and auditory hallucinations. The intervention was delivered in six sessions over three days. Outcomes were assessed using the Auditory Hallucination Rating Scale (AHRS) and clinical observation before and after the intervention. The AHRS score decreased from 30 (severe) before the intervention to 25 on the second day and 23 on the third day, indicating reduced hallucination severity. The client also showed improved concentration, greater participation in therapy, and better control of auditory hallucinations during drawing sessions. These findings suggest that drawing-based occupational therapy may be a useful supportive intervention in psychiatric nursing care, although further studies with larger samples are needed